The Mediation Effect Of Strategic Planning On The Relationship Between Business Skills And Firm’s Performance: Evidence From Medium Enterprises in Punjab, Pakistan - Shuhymee Bin Ahmad, Israr Ahmad, (Opción, 2019)
The study aims are to examine the mediating effect of strategic Planning (SP) on the relationship of business skills and performance of medium enterprises’ (MEs) via the quantitative research method. This study finds that strategic planning has a significantly positive impact on the relationship of business skills and MEs’ performance in Punjab, Pakistan. In conclusion, it was ascertained that strategic planning is the only factor that can assist to boost company performance.